Rotation thromboelastometry analysis of clot formation and fibrinolysis in severe thrombocytopenia: effect of fibrinogen, activated prothrombin complex concentrate, and thrombin‐ activatable fibrinolysis inhibitor. (4th February 2015) - Shenkman, B.; Einav, Y.; Livnat, T.; Budnik, I.; Martinowitz, U.
Summary Introduction Bleeding symptoms in severe thrombocytopenia range from mild to severe. The aim of this in vitro study was to improve blood clotting and protect against fibrinolysis in reconstituted severe thrombocytopenia blood. Methods Thrombocytopenia [(16 ± 4) × 106/mL] was created by high‐speed centrifugation of normal blood with subsequent mixing plasma with packed cells. The blood samples were subjected to clotting by CaCl2 and tissue factor and to fibrinolysis by the addition of tissue plasminogen activator. Blood was spiked with fibrinogen, activated prothrombin complex concentrate (FEIBA), thrombin activatable fibrinolysis inhibitor (TAFI), or their combinations. To mimic the situation that may occur in patients subjected to massive transfusion of plasma substitutes, blood was diluted by 40% of TRIS/saline buffer. Clotting time (CT), α‐Angle, maximum clot firmness (MCF), and lysis onset time (LOT) were evaluated using rotation thromboelastometry. Results Spiking thrombocytopenia blood with FEIBA led to reduction of CT. Fibrinogen and FEIBA enhanced α‐Angle and MCF both in the absence and in the presence of tPA. LOT values were prolonged by TAFI and to less extent by FEIBA. Dilution of thrombocytopenia blood was followed by reduction of α‐Angle and MCF compared to nondiluted blood which partly reversed by either fibrinogen or FEIBA being higher using fibrinogen and FEIBA together. Clot strength was enhanced, and fibrinolysis was inhibited by TAFI. Conclusion The results of this study suggest that combined spiking of blood with fibrinogen and FEIBA may be enough to correct the clot formation disorder in severe thrombocytopenia, whereas in thrombocytopenia and blood dilution, additive inhibition of fibrinolysis may be needed.